Method of efficiently predicting the conducted emissions of multiple VSCs - Ivry, Preye Milton; Oke, O.A.; Thomas, David W.P.; Sumner, M. (2014)
Various types of power converters including Voltage Source Converters (VSCs) have been known to produce conducted emissions. The net effect of simultaneously operating multiple VSCs is non-linear and this makes the prediction of the emission level more difficult. This paper presents an efficient method that can be used to predict conducted emissions of multiple VSCs in the presence of various uncertainties. It utilizes the Univariate Dimension Reduction (UDR) and the Bivariate Dimension Reduction (BDR) technique to predict the conducted emission level of multiple VSCs.